ANIMALS AS A SUBJECT OF REGISTERED STOCKS - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Summary: The adoption of the law that has introduced non-possessory lien securing the movable property and rights (colloquially called Act on registered pledge), allowed the commitment of animals, through registration in the register of stocks in the Business Registers Agency. The topic has been chosen, both because of the practical reasons (more and more domestic animals are being registered as collaterals in the Register), and because there are no articles on this topic in our legal science. In the article the emphasis is placed on the regulation of the legal status of animals, especially in the Act on registered bets, the Law on Obligations and Preliminary Draft of Serbian Civil Code. Special attention was devoted to the Animal Welfare Act, because of the provisions of this legal regulation that follow a series of obligations for the sides in the contract of registered pledge, as well as certain restrictions with regard to the animal as an object of inventory. Although our legislature is obliged, in accordance with the obligation of harmonizing national legal regulations with EU regulations, to implement higher standards in the treatment of animals as beings who have feelings, it is only partially done in our law. Draft Civil Code retains an approach that had the Law of Obligations Act 1978, treating animals as classical chattel. Such an approach has been abandoned in all the most important civil codification. The paper presents the proposals relating to the improvement of the existing legislation in this area. Proposals for amending the Law on registered pledges are defined in relation to issues not resolved by this piece of legislation, such as the question of the legal status of unborn offspring. It points to the practices of the Agency for Business Registers that is not based on law, which involves entering the maximum amount of credit to pledge any security. Despite the Act did not define the registered pledge restrictions in the case of animal advocacy, the paper, by applying provisions of the Animal Welfare Act, indicates which species should be excluded from the circle of potential subjects of pledge security, but also indicates the species that have not been registered ever, without obvious practical reasons, or formal ban.